(untitled) (Studia Prawnicze / The Legal Studies, 1963)
The new structure of the organization of state-owned enterprises according to the decree on state-owned enterprises, amended in 1960, substitutes the previous form of their management and supervision, through the mediation of central administrations formally included in the composition of the economic ministries and overly limiting the independence of these enterprises, with a new organizational form. This consists of a grouping of state-owned enterprises into economic units, assigning them the functions of supervision and coordination in relation to the grouped enterprises. This new form of organisation is called a Union. The Union is headed by a Director. But, a characteristic for the new form is a body of advice that gives its advice and opinions. The directors of the enterprises grouped in the Union take part in the advisory body. However, the Statute of the Union provides for cases where the resolutions of the board come into force and are binding on the director and the grouped enterprises. What is the nature of the legal relationship between the Union and the grouped enterprises? In order to answer this question, the following should be highlighted: • the Union of Enterprises forms a homogeneous economic organisation; • the Union is a superior unit in relation to the grouped enterprises or, in other words, a state administration body, exercising supervision, control and coordination of their activity. This last characteristic of the Union undoubtedly prejudges the legal title of the administrative and financial relations between the Union and the grouped enterprises. However, the organization of the Union’s council body, as well as the way of assuming its resolutions and their character, have the purpose of realizing the democratic centralism in the administration of our national economy through the participation and influence of the interested companies on the activity of the main bodies – of the Unions and, what follows, on the decisions and resolutions that they undertake. The scope of application of civil law regulations can be observed only in the narrow field of relations between the Union and the grouped enterprises.